Farmers’ responses to global warming - Robles Mendoza, Román (2014)
In this work we try show on micro spaces, socio-economic effects of global warming. Our purpose is to record what aspects of the daily life of Andean peasants have meaning climate change. Clearly, it is in agriculture, main activity on which is based the peasant life, which it receive our attention. For this purpose we have moved to three regions to investigate in situ the process of change, as a sample. In localities visited we observed directly the natural and cultural landscapes, we have spoken with active farmers and intermediaries linked to the market and with communities and district authorities. The result of our research is the finding that the phenomenon of global warming has a concrete impact on the daily practice of agriculture, both crop substitution and plantations as well as cultural practices concomitant with these changes. The remarkable thing about these changes is the substitution of fruit for traditional crops like corn, but also the advancement of corn cultivation into areas that were previously dedicated to potatoes and cereals. Against this process of change, it appears that the social actors of the villages visited slowly adapt to climate change. Several of these changes go unnoticed and appear as new experiences that give unexpected results. Specifically, these innovations are more common in the crop system and new experiences in food consumption.